Manajemen Aset sebagai Mediator Pengaruh Likuiditas dan Solvabilitas terhadap Profitabilitas Perusahaan Pertambangan Batubara - Atri Nodi Maiza Putra; Ujang Kusnaedi; Nurhayati Nurhayati; Wanda Afrianti (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to examine the effect of liquidity and solvency on profitability, with asset management acting as a mediating variable in coal mining companies listed on the Indonesia Stock Exchange during the 2021–2024 period. The research employed a quantitative approach using secondary data obtained from the companies’ annual financial statements. The sample consisted of 10 companies selected through purposive sampling, resulting in 40 firm-year observations in a balanced panel dataset. Liquidity was measured using the Current Ratio (CR), solvency was proxied by the Debt-to-Equity Ratio (DER), asset management was measured through Total Asset Turnover (TATO), and profitability was assessed using Return on Assets (ROA). Path analysis was applied to examine both direct and indirect effects among variables, and the Sobel test was used to determine the mediating role of asset management. The results indicate that liquidity and solvency significantly affect profitability both directly and indirectly through asset management. Asset management is proven to mediate the relationship between financial structure and corporate profitability. These findings highlight the importance of efficient asset management in enhancing financial performance in capital-intensive industries such as coal mining.